Marxism and phenomenology the dialectical horizons of critique - Smyth, Bryan, 1969-; Westerman, Richard, 1978- (Continental philosophy and the history of thought, 2022)
"This volume examines various points of contact between Marxism and phenomenology. Although these traditions can appear conceptually incompatible, the contributors reveal productive complementarities on themes such as alienation, reification, and ecology, which illuminate and can help to resolve the crises of contemporary capitalism"--